2006
DOI: 10.1196/annals.1354.030
|View full text |Cite
|
Sign up to set email alerts
|

Aging of Murine Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are able to differentiate into distinct lineages such as adipo-, osteo-, and chondrocytes. MSCs were isolated from three mouse strains, which are short- (SAMP6, 9.7 months), medium- (SAMR1, 16.3 months), or long-lived (C57BL/6, 28 months). We investigated primary colony-forming units with regard to bone marrow stroma and found differences that correlate with mean life expectancies of the particular genetic backgrounds. However, MSC derived from the various mouse strains behaved eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
5
27
1
1
Order By: Relevance
“…The molecular mechanisms of this "Hayflick limit" are yet unknown. Certainly, molecular profiles and functional features of MSC are affected by this process of cellular aging [49][50][51]. Cell density of cultures seems to be crucial, too.…”
Section: In Vitro Cultivation (Passage Density and Cryopreservation)mentioning
confidence: 98%
“…The molecular mechanisms of this "Hayflick limit" are yet unknown. Certainly, molecular profiles and functional features of MSC are affected by this process of cellular aging [49][50][51]. Cell density of cultures seems to be crucial, too.…”
Section: In Vitro Cultivation (Passage Density and Cryopreservation)mentioning
confidence: 98%
“…17,18 It has been suggested that MSCs from different mouse strains (SAMP6, SAMR1, C57BL/6) with different life expectancies may be intrinsically similar in their in vitro proliferation and differentiation capacity, despite exhibiting dramatically different in vivo differentiation and proliferation capacity due to the influence of heterogeneous microenvironments. 19 Furthermore, age is associated with changes in the ECM that have been linked to multiple pathologies (reviewed in ref. 20 ), including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, molecular pro fi les and functional features of MSC are signi fi cantly affected by this process of cellular aging (DiGirolamo et al 1999 ;Fehrer et al 2006 ;Javazon et al 2004 ;Wagner et al 2008Wagner et al , 2009 . Cell density of cultures seems to be crucial, too.…”
Section: In Vitro Cultivation (Passage Density and Cryopreservation)mentioning
confidence: 99%